The Influence of Different Fat Sources on Steatohepatitis and Fibrosis Development in the Western Diet Mouse Model of Non-alcoholic Steatohepatitis (NASH) - Drescher, Hannah K.; Weiskirchen, Ralf; Fülöp, Annabelle; Hopf, Carsten; de San Román, Estibaliz González; Huesgen, Pitter F.; de Bruin, Alain; Bongiovanni, Laura; Christ, Annette; Tolba, René; Trautwein, Christian; Kroy, Daniela C. (Frontiers in Physiology, 2019)
Non-alcoholic steatohepatitis (NASH) is the leading cause of chronic liver injury and the third most common reason for liver transplantations in Western countries. It is unclear so far how different fat sources in Western diets (WD) influence the development of non-alcoholic steatohepatitis. Our study investigates the impact of non trans fat (NTF) and corn oil (Corn) as fat source in a WD mouse model of steatohepatitis on disease development and progression. C57/B6J wildtype (WT) mice were fed “standard” WD (WD-Std), WD-NTF or WD-Corn for 24 weeks. WT animals treated with WD-NTF exhibit distinct features of the metabolic syndrome compared to WD-Std and WD-Corn. This becomes evident by a worsened insulin resistance and elevated serum ALT, cholesterol and triglyceride (TG) levels compared to WD-Corn. Animals fed WD-Corn on the contrary tend to a weakened disease progression in the described parameters. After 24 weeks feeding with WD-NTF and WD-Std, WD-Corn lead to a comparable steatohepatitis initiation by histomorphological changes and immune cell infiltration compared to WD-Std. Immune cell infiltration results in a significant increase in mRNA expression of the pro-inflammatory cytokines IL-6 and TNF-α, which is more pronounced in WD-NTF compared to WD-Std and WD-Corn. Interestingly the fat source has no impact on the composition of accumulating fat within liver tissue as determined by matrix-assisted laser desorption/ionization mass spectrometry imaging of multiple lipid classes. The described effects of different fat sources on the development of steatohepatitis finally resulted in variations in fibrosis development. Animals treated with WD-NTF displayed massive collagen accumulation, whereas WD-Corn even seems to protect from extracellular matrix deposition. Noteworthy, WD-Corn provokes massive histomorphological modifications in epididymal white adipose tissue (eWAT) and severe accumulation of extracellular matrix which are not apparent in WD-Std and WD-NTF treatment. Different fat sources in WD-Std contribute to strong steatohepatitis development in WT mice after 24 weeks treatment. Surprisingly, corn oil provokes histomorphological changes in eWAT tissue. Accordingly, both WD-NTF and WD-Corn appear suitable as alternative dietary treatment to replace “standard” WD-Std as a diet mouse model of steatohepatitis whereas WD-Corn leads to strong changes in eWAT morphology.